The influence of absent crowds on national rugby league match player statistics and running metrics - Fazackerley, L.; Gorman, A.; Minett, G.; Caia, J.; Kelly, V. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: The novel strain of coronavirus disease, COVID-19, was first identified in 2019, and due to its highly contagious nature, many elite sporting competitions were suspended and/or postponed. Sporting events that could continue, whether immediately or delayed, implemented strict bio-safety precautions to minimise the risk of spreading infection. Consequently, in many cases, crowds were prohibited from attending games. Research suggests that the presence or absence of a crowd may exert a social facilitation effect on players and officials in elite sport, which in turn might affect performance. Along with social facilitation theory, a related phenomenon known as the home advantage, suggests that the home team typically wins more games and scores more points than the away team. Research suggests that supportive crowds are social representatives of their players and encourage the home team to play well. However, minimal research has investigated the interaction between crowd (present or absent) and match location (home or away) on sport performance.